AN OVERVIEW OF FIRST AID BEHAVIOR IN TODDLER CHILDREN WHO FELL IN THE WORKING AREA OF THE BERAKIT PUBLIC HEALTH CENTER 2021 - Elsa Gusrianti; Rian Yuliyana; Indah Dwi Astuti; Asmarita Jasda (Bajang Institute, 2021)
Children aged 1 to 3 years are the most critical period because 80% of brain growth occurs at that age or known as the Golden age (Nursalam, 2005). Based on the stages of growth and development of toddler-age children, it is necessary to get supervision from parents because in carrying out their activities children do not pay attention to the dangers that exist around them (Nursalam, 2005). According to dinkes Kepri (2014), the prevalence of injury events in toddler-aged children is injury (8.9%), drowning accidents (20.6%), bone fractures (2.6%), burns (5.3%), foreign body entry (9.7%), unexpected injuries (8.7%), and poisoning (10.26%). Toddler injuries can be prevented, one of which is with good supervision from parents (Arvin, 2000). This study aims to provide an overview of first aid behavior in toddler children who fall in the work area of the rafted health center. The total sample of this study was 30 people. The sampling technique uses a non-probability technique, namely a saturated sample or often called total sampling, where all members of the population are used as samples. In this study, it was known that respondents had alevel of good behavior (80%). This is influenced by several factors, namely education, sources of information, and experience. The results of this study are expected to add insight, contribute to science, especially those related to the problem of first aid in fallen toddler children and contribute thoughts for parents regarding first aid in fallen toddler children.